Angelina and Alice - Holabird, Katharine (Holabird, Katharine. Angelina Ballerina., 2021)
"Angelina and Alice love doing gymnastics together. But when Angelina can't do a handstand, all the older children laugh--and Alice giggles too. Can Angelina and Alice still stay best friends?" -- Page [4] of cover.